Kajian Kesejahteraan Hewan dan Hubungannya dengan Karakteristik Peternak pada Peternakan Kambing di Manokwari - Zurahmah, N; Masriani, M (Politeknik Negeri Lampung, 2024)
This study aims to assess the level of welfare of goats kept intensively in Manokwari, and to analyze the relationship with characteristics of traditional farmers and the level of welfare of the goats they keep. The research was conducted in an area densely populated with goats (Prafi and Masni districts), in Manokwari. The research sample of 21 goat farms, selected by purposive sampling, was used in this study. Animal welfare assessment was carried out using the Animal Needs Index (ANI) method which was modified according to goats. The results showed that only 33% of goat farms in the study area were classified as prosperous. There is a significant relationship (P<0.05) between age and rearing scale with the welfare level of the goats they keep. Therefore, it is necessary to pay attention to the age of the breeder and the scale of rearing goats in Manokwari in an effort to improve the welfare of the goats kept.